Facile Synthesis of Ultralong and Thin Copper Nanowires and Its Application to High-Performance Flexible Transparent Conductive Electrodes - Yaxiong Wang; Ping Liu; Baoqing Zeng; Liming Liu; Jianjun Yang (Nanoscale Research Letters, 2018)
Abstract A hydrothermal method for synthesizing ultralong and thin copper nanowires (CuNWs) with average diameter of 35 nm and average length of 100 μm is demonstrated in this paper. The concerning raw materials include copric (II) chloride dihydrate (CuCl2·2H2O), octadecylamine (ODA), and ascorbic acid, which are all very cheap and nontoxic. The effect of different reaction time and different molar ratios to the reaction products were researched. The CuNWs prepared by the hydrothermal method were applied to fabricate CuNW transparent conductive electrode (TCE), which exhibited excellent conductivity-transmittance performance with low sheet resistance of 26.23 Ω/□ $\Omega /\square $ and high transparency at 550 nm of 89.06% (excluding Polyethylene terephthalate (PET) substrate). The electrode fabrication process was carried out at room temperature, and there was no need for post-treatment. In order to decrease roughness and protect CuNW TCEs against being oxidized, we fabricated CuNW/poly(methyl methacrylate) (PMMA) hybrid TCEs (HTCEs) using PMMA solution. The CuNW/PMMA HTCEs exhibited low surface roughness and chemical stability as compared with CuNW TCEs.